2021
DOI: 10.1007/s12975-020-00879-w
|View full text |Cite
|
Sign up to set email alerts
|

Recanalization Therapy for Acute Ischemic Stroke with Large Vessel Occlusion: Where We Are and What Comes Next?

Abstract: In the past 5 years, the success of multiple randomized controlled trials of recanalization therapy with endovascular thrombectomy has transformed the treatment of acute ischemic stroke with large vessel occlusion. The evidence from these trials has now established endovascular thrombectomy as standard of care. This review will discuss the chronological evolution of large vessel occlusion treatment from early medical therapy with tissue plasminogen activator to the latest mechanical thrombectomy. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 114 publications
(252 reference statements)
0
25
0
1
Order By: Relevance
“…Randomized and controlled trials have demonstrated that AIS patients treated with EVT had a higher rate of successful recanalization, more favorable clinical outcomes, and longer therapeutic window compared with thrombolytic therapy [ 2 , 3 ]. However, futile recanalization, which is defined as patients having unfavorable outcomes (mRS of 3–6) despite successful recanalization (mTICI of 2b–3), remains a major clinical challenge to predict and is poorly understood [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Randomized and controlled trials have demonstrated that AIS patients treated with EVT had a higher rate of successful recanalization, more favorable clinical outcomes, and longer therapeutic window compared with thrombolytic therapy [ 2 , 3 ]. However, futile recanalization, which is defined as patients having unfavorable outcomes (mRS of 3–6) despite successful recanalization (mTICI of 2b–3), remains a major clinical challenge to predict and is poorly understood [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, futile recanalization, which is defined as patients having unfavorable outcomes (mRS of 3–6) despite successful recanalization (mTICI of 2b–3), remains a major clinical challenge to predict and is poorly understood [ 4 , 5 ]. There is no reliable clinical, blood, or radiological markers to predict outcomes after EVT [ 3 , 32 ], except for more generic measurements such as age, stroke severity, general anesthesia, and hyperglycemia (glycated hemoglobin > 6.5%) for predicting poor prognosis of patients after EVT [ 5 , 32 ]. Biomarkers detected in the peripheral blood of patients could have better predictive values because they are often related to pathophysiological response to EVT recanalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective treatment time window of rt-PA is 4.5 h, and patients with large artery occlusion can be treated with thrombectomy within 6 h or even beyond 24 h of symptom onset. However, nearly 60% of patients did not achieve functional independence at 3 months after treatment in recent mechanical thrombectomy trials ( Rabinstein, 2020 ; Shafie and Yu, 2021 ). When ischemic stroke occurs, apoptosis or necrosis of various cells is seen in the infarct areas.…”
Section: Introductionmentioning
confidence: 99%
“…The major success stories for treating brain injury have been the use of thrombolytic therapy and endovascular thrombectomy for ischemic stroke [1][2][3]. As a therapy, thrombectomy has been approved for a much shorter time than thrombolysis and, as reviewed by Shafie and Yu [4], we are still exploring the limits of thrombectomy as a therapy. As described by Kang et al [5], one big question is the therapeutic time window and the extent to which imaging can identify patient sub-populations that will benefit from delayed thrombectomy.…”
mentioning
confidence: 99%